2019
DOI: 10.1097/scs.0000000000005204
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Surgical Planning and Three-Dimensional Printed Guide for Soft Tissue Correction in Facial Asymmetry

Abstract: Fat grafting has become a well-accepted surgical modality to correct soft tissue facial defects and asymmetries with overall good results. Several techniques have been reported over the last few years to assist in improving accurate evaluation of facial defects and in the preoperative planning of the reconstruction. Such techniques include among others, computer tomography, three-dimensional (3D) photogrammetry, high resolution ultrasound, and 3D laser scanning. There are advantages and disadvantages for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…9,13 For example, the fabrication of intra-operative surgical masks, similar to the one used in our patient, has been shown to be beneficial in the correction of facial asymmetry regardless of etiology. [13][14][15] Furthermore, virtual imaging and mathematical calculations can provide more accurate and precise values for facial volume adjustment than traditional methods. 9,13,16 This is critical in facial surgery, where even subtle changes can have a significant impact on overall appearance.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…9,13 For example, the fabrication of intra-operative surgical masks, similar to the one used in our patient, has been shown to be beneficial in the correction of facial asymmetry regardless of etiology. [13][14][15] Furthermore, virtual imaging and mathematical calculations can provide more accurate and precise values for facial volume adjustment than traditional methods. 9,13,16 This is critical in facial surgery, where even subtle changes can have a significant impact on overall appearance.…”
Section: Discussionmentioning
confidence: 82%
“…Finally, although not unique to soft tissue applications, VSP and CAD/CAM technology comes with increased initial costs, and requires time and surgeon familiarity for successful implementation. 12-14…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arias et al reported a 3D printed surgical guide to define volume differences for soft tissue reconstruction in patients with facial asymmetry. 16 The simulated postoperative mask was exported to stereolithographic files for printing and 3D printed in a clear photopolymerizing resin. The mask was used by the surgeon at the end of the procedure and during follow-up.…”
Section: Discussionmentioning
confidence: 99%